First by simplifying step by step
2.8k-8.4
There are no like terms.
Answer is = 2.8k-8.4
Look at the attachment!
Thanks. (I can’t see the Tuesday 24 Question 5, sorry.)
I would try B.
I'm not positive i got it right
(sorry if its wrong)
Hope this helped!
:)
Answer:
x=
−4y+32
9
Step-by-step explanation:
Let's solve for x.
y=
−9
4
x+8
Step 1: Flip the equation.
−9
4
x+8=y
Step 2: Add -8 to both sides.
−9
4
x+8+−8=y+−8
−9
4
x=y−8
Step 3: Divide both sides by (-9)/4.
−9
4
x
−9
4
=
y−8
−9
4
x=
−4y+32
9
I think this is the right answer.
Answer:
![\displaystyle \begin{cases} \displaystyle {x} _{1} = - p \\ \displaystyle x _{2} = - q \end{cases}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%20%5Cbegin%7Bcases%7D%20%5Cdisplaystyle%20%20%7Bx%7D%20_%7B1%7D%20%3D%20%20-%20p%20%5C%5C%20%20%20%5Cdisplaystyle%20x%20_%7B2%7D%20%20%20%3D%20%20-%20%20q%20%5Cend%7Bcases%7D)
Step-by-step explanation:
we would like to solve the following equation for x:
![\displaystyle \frac{1}{p} + \frac{1}{q} + \frac{1}{x} = \frac{1}{p + q + x}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%5Cfrac%7B1%7D%7Bp%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7Bq%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7Bx%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7Bp%20%20%2B%20q%20%2B%20x%7D%20)
to do so isolate
to right hand side and change its sign which yields:
![\displaystyle \frac{1}{p} + \frac{1}{q} = \frac{1}{p + q + x} - \frac{1}{x}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%5Cfrac%7B1%7D%7Bp%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7Bq%7D%20%20%20%20%3D%20%20%5Cfrac%7B1%7D%7Bp%20%20%2B%20q%20%2B%20x%7D%20%20-%20%20%5Cfrac%7B1%7D%7Bx%7D%20)
simplify Substraction:
![\displaystyle \frac{1}{p} + \frac{1}{q} = \frac{x - (q + p + x)}{x(p + q + x)}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%5Cfrac%7B1%7D%7Bp%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7Bq%7D%20%20%20%20%3D%20%20%5Cfrac%7Bx%20-%20%28q%20%2B%20p%20%2B%20%20x%29%7D%7Bx%28p%20%20%2B%20q%20%2B%20x%29%7D%20%20)
get rid of only x:
![\displaystyle \frac{1}{p} + \frac{1}{q} = \frac{ - (q + p )}{x(p + q + x)}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%5Cfrac%7B1%7D%7Bp%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7Bq%7D%20%20%20%20%3D%20%20%5Cfrac%7B%20%20-%20%28q%20%2B%20p%20%29%7D%7Bx%28p%20%20%2B%20q%20%2B%20x%29%7D%20%20)
simplify addition of the left hand side:
![\displaystyle \frac{q + p}{pq} = \frac{ - (q + p )}{x(p + q + x)}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%5Cfrac%7Bq%20%2B%20p%7D%7Bpq%7D%20%20%20%20%20%3D%20%20%5Cfrac%7B%20%20-%20%28q%20%2B%20p%20%29%7D%7Bx%28p%20%20%2B%20q%20%2B%20x%29%7D%20%20)
divide both sides by q+p Which yields:
![\displaystyle \frac{1}{pq} = \frac{ -1}{x(p + q + x)}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%5Cfrac%7B1%7D%7Bpq%7D%20%20%20%20%20%3D%20%20%5Cfrac%7B%20%20-1%7D%7Bx%28p%20%20%2B%20q%20%2B%20x%29%7D%20%20)
cross multiplication:
![\displaystyle x(p + q + x) = - pq](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%20%20x%28p%20%20%2B%20q%20%2B%20x%29%20%20%3D%20%20%20-%20pq)
distribute:
![\displaystyle xp + xq + {x}^{2} = - pq](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%20%20xp%20%20%2B%20xq%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%3D%20%20%20-%20pq)
isolate -pq to the left hand side and change its sign:
![\displaystyle xp + xq + {x}^{2} + pq = 0](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%20%20xp%20%20%2B%20xq%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%2B%20pq%20%3D%20%200)
rearrange it to standard form:
![\displaystyle {x}^{2} + xp + xq + pq = 0](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%20%7Bx%7D%5E%7B2%7D%20%2B%20%20%20%20xp%20%20%2B%20xq%20%20%2B%20pq%20%3D%20%200)
now notice we end up with a <u>quadratic</u><u> equation</u> therefore to solve so we can consider <u>factoring</u><u> </u><u>method</u><u> </u><u> </u>to use so
factor out x:
![\displaystyle x( {x}^{} + p ) + xq + pq = 0](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20x%28%20%7Bx%7D%5E%7B%7D%20%2B%20%20%20p%20%29%20%2B%20xq%20%20%2B%20pq%20%3D%20%200)
factor out q:
![\displaystyle x( {x}^{} + p ) +q (x + p)= 0](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20x%28%20%7Bx%7D%5E%7B%7D%20%2B%20%20%20p%20%29%20%2Bq%20%28x%20%2B%20p%29%3D%20%200)
group:
![\displaystyle ( {x}^{} + p ) (x + q)= 0](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%28%20%7Bx%7D%5E%7B%7D%20%2B%20%20%20p%20%29%20%28x%20%2B%20q%29%3D%20%200)
by <em>Zero</em><em> product</em><em> </em><em>property</em> we obtain:
![\displaystyle \begin{cases} \displaystyle {x}^{} + p = 0 \\ \displaystyle x + q= 0 \end{cases}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%20%5Cbegin%7Bcases%7D%20%5Cdisplaystyle%20%20%7Bx%7D%5E%7B%7D%20%2B%20%20%20p%20%20%3D%200%20%5C%5C%20%20%20%5Cdisplaystyle%20x%20%2B%20q%3D%20%200%20%5Cend%7Bcases%7D)
cancel out p from the first equation and q from the second equation which yields:
![\displaystyle \begin{cases} \displaystyle {x}^{} = - p \\ \displaystyle x = - q \end{cases}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%20%5Cbegin%7Bcases%7D%20%5Cdisplaystyle%20%20%7Bx%7D%5E%7B%7D%20%20%20%3D%20%20-%20p%20%5C%5C%20%20%20%5Cdisplaystyle%20x%20%20%3D%20%20-%20%20q%20%5Cend%7Bcases%7D)
and we are done!